THE RATU BOKO MANTRA AND THE SAILENDRAS - Roy Jordaan; Brian Colless (Berkala Arkeologi, 2004)
The Ratu Boko (or Ratu Baka) plateau, near Yogyakarta in southern central Java, is surrounded by an impressive array of Hindu and Buddhist shrines. Notable among these are the Prambanan temples to the north, and Candi Kalasan to the west, with the massive Borobudur stupa 40 kilometres to the northwest, and the lofty volcanoes Merapi and Merbabu towering over the northern landscape. The presence of dynamic mountains and Buddhist monuments makes the Ratu Boko heights an ideal spot for locating the lost palace of the Sailendra 'mountain lords', though they may well have resided on the plain or in a northern port. However that may be, Ratu Boko was the site of the famous Sailendra monastery, Abhayagirivihara, which had links with Sri Lanka.